Theoretical, Psychological, and Philosophical Interrelation in Mathematics Learning through YouTube for Elementary School Students - Sri Hartatik; Nafiah Nafiah; Pance Mariati (AL-ISHLAH: Jurnal Pendidikan, 2023)
Modern education integrates several aspects as a single unit of learning, especially for elementary school students. This study identifies the interrelation of art, technology, education, and mathematics for elementary school students. A new style of education that incorporates both the arts and the sciences is also considered in this research: interactive learning. Using netnography, this investigation takes a multi-site qualitative approach. Furthermore, the study was conducted by conducting netnographic observations on the YouTube channel with the keyword "Elementary School Mathematics (language: Indonesian)" during July 2021 and analyzed by conducting a theoretical exploration of art, psychological, and philosophical interrelationship technology education. The results show that the interrelation that occurs begins with elaborating aspects of the STEAM approach, which at each point is in learning through art technology on YouTube. This contributes psychologically and affects children's critical thinking skills. Furthermore, there is a postphenomenological aspect as an outcome of the interrelation that occurs.